Effect of long‐term loading and fire temperatures on mechanical properties of concrete - Jonaitis, Bronius; Papinigis, Vytautas (Journal of Civil Engineering and Management, 2005)
During a fire, reinforced concrete structures are exposed to high temperatures and subjected to long‐term action of variable and permanent loads. This paper deals with analysis of influence of fire temperatures and long‐term action of loads on compression strength and deformability of normal weight concrete. Results of experimental investigations of compression strength and deformability of normal‐weight concrete subjected to long‐term load and exposed to high temperature are presented. Specimens in the shape of prisms of normal‐weight concrete were subjected to long‐term compression of intensity η(t) = σc/fc (τ) = 0,3. The long‐term compression was sustained for 400 days. Some of the specimens were heated (at 250 °C and 450 °C) before application of long‐term load; other specimens were heated after application of long‐term load. The paper presents coefficient of service conditions for concrete subjected to long‐term load and exposed to high temperature that gives opportunity to evaluate compression strength and deformation properties of concrete. Ilgalaikės apkrovos ir gaisro temperatūrų įtaka betono mechaninėms savybėms Santrauka. Nagrinėjamas gaisro temperatūrų ir ilgalaikės apkrovos poveikis sunkiojo betono gniuždomajam stipriui ir deformacinėms savybėms. Pateikiami ilgalaike apkrova ir aukšta temperatūra paveikto sunkiojo betono stiprumo ir deformacijų tyrimo rezultatai. Sunkiojo betono bandiniai – prizmės, apkrautos ilgalaike gniuždančia apkrova, kurios intensyvumas η = σc/fc = 0,3. Ilgalaikių bandymų trukmė – 400 parų. Dalis bandinių kaitinti (temperatūra 250 °C ir 450 °C), prieš juos apkraunant ilgalaike apkrova, kiti bandiniai kaitinti po to, kai buvo apkrauti šia apkrova. Pateikiami ilgalaike apkrova ir aukšta temperatūra paveikto betono patikimumo koeficientai, leidžiantys įvertinti betono gniuždomąjį stiprį ir deformacines savybes. Reikšminiai žodžiai: betonas, ilgalaikė apkrova, gaisro temperatūros, gniuždomasis stipris, deformacijos. First Published Online: 14 Oct 2010